Exploring the patterns of multisectoral approach in fighting COVID-19 Pandemic in SNNPR, Ethiopia: A qualitative case study approach - Abraham A. Ali; Akmel M. Usman; Fekadeselassie B. Badebo; Solomon H. Tilahun (PLoS ONE, 2022)
Background Since COVID-19 has been declared as a global pandemic, South Nations, Nationalities People’s Region, Ethiopia, has been responding by establishing strong structure. The response against the disease requires consolidated efforts, However, there is paucity of information about the patterns of multisectoral collaboration actions in the region. Therefore, this study was conducted with the aim of exploring the patterns of multisectoral collaboration against the COVID-19 using a qualitative case study design. Data were collected by key informant interview and document review and analyzed using a content analysis framework focused on case study data analysis. Result The study has indicated a unique perspective in establishing functional multisectoral approach with strong courage and motivation of most involved stakeholder. Almost all stakeholders have shown clear understanding about the multidimensional burdens the disease could cause and the necessities for joint efforts to tackle the multidimensional problems. The study further elucidated that despite the encouraging beginning, the eventual slowdown undertakings in the joint actions. This included failure to meet regularly to monitor and evaluate as stated earlier and societies’ reluctances despite consistent information dissemination. Conclusion A firm understanding about multidimensional impacts of COVID-19 by all stakeholders was revealed in the region. Remarkable achievements were observed at the early stage of disease prevention and control responses with encouraging multisectoral approach as guided by the convergence model. However, several setbacks were observed in the process of multisectoral approach intervention as indicated by the conceptual framework. Hence, to ensure sustainable MSA, revitalization of the initial commitment of all stakeholders and strengthening MSA considering end-to end approach of the convergence frame is crucial; subsequent quantitative study recommended to establish wider determinants on success of MSA.